2018
DOI: 10.24832/papua.v9i1.205
|View full text |Cite
|
Sign up to set email alerts
|

SITUS NEOLITIK MALLAWA MAROS, SULAWESI SELATAN (Suatu Hasil Analisis Keterkaitan antara Artefak dengan Sumber Daya Lingkungan) Neolithic Site at Mallawa Maros of South Sulawesi [A Result of Relevancy Analysis Between The Artefacts and The Environment Resources]

Abstract: The Mallawa is an open site located in the eastern part of Maros, South Sulawesi. The topography of Mallawa site is wavy and took place in a hilly area. Dating of the site using C14 Analysis showed that the site is about 3550 ±130 BP and 2710 ±170 BP and 2281± 46 BP. The point of this site, besides of its plenty artifacts that signifying occupied-densely site of some hills, the site is also located nearby caves of Maros. From the perspective of periodization, Mallawa site relatively younger compared to occupan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The footprint of Austronesian culture in Mallawa has already been detected through previous research such as Simanjuntak (2008), Hakim et al (2009 and Hasanuddin (2017a). Until now the earliest signs of Austronesian culture in Mallawa are known from the Bulu Bakung site with dates of 3580±130 BP and 2710±170 BP (Simanjuntak 2008:233).…”
Section: Austronesian Culture In Mallawamentioning
confidence: 75%
See 2 more Smart Citations
“…The footprint of Austronesian culture in Mallawa has already been detected through previous research such as Simanjuntak (2008), Hakim et al (2009 and Hasanuddin (2017a). Until now the earliest signs of Austronesian culture in Mallawa are known from the Bulu Bakung site with dates of 3580±130 BP and 2710±170 BP (Simanjuntak 2008:233).…”
Section: Austronesian Culture In Mallawamentioning
confidence: 75%
“…Its calibrated date in the seventh millennium BP (Table 5) therefore applies to either the late accumulation of sandy silt or to the early accumulation of coarse sand at Liang Uttange 1. (Hasanuddin 2017a). The research of Duli et al (2015) also demonstrated the existence of cultural layers at the Liang Panninge site that contained both Maros points and microliths.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Surveys and excavations at the Bulu Bakung open site both earlier [11] and in 2019, show a high intensity of findings, reflecting occupancy in open areas. Unlike the findings in rock shelters in the same area, the findings at the Bulu Bakung Site (open site) are only in the form of stone artifacts and pottery.…”
Section: Cultural Diversitymentioning
confidence: 94%
“…The time span of using pottery in Mallawa represented by Bulu Bakung sites aged 3580 ± 130 BP [22,16]. This was made possible using local raw materials at the Bulu Bakung Site and its surroundings as evidenced by the suitability of the compound (XRF) [11].…”
Section: Introductionmentioning
confidence: 99%